IMPACT OF ESG DISCLOSURE ON STOCK RETURNS IN COMPANIES LISTED ON INDONESIA STOCK EXCHANGE - Herly Nurlinda; Yanti Yanti (International Journal of Application on Economics and Business, 2026)
As the growing concern over climate change and environmental issues, investors increasingly seek investments that not only to accumulate yield of stock returns but also to have a positive contribution harmoniously with the Sustainable Development Goals (SDGs) continuously. In the context within business and financial cores, the SDGs are supported by Environmental, Social, and Governance (ESG) disclosures, emerging to serves as a parameter for evaluating an organization’s contribution to environmental and social aspects through good corporate governance. The limited research on the relationship impact between ESG disclosure and stock returns in Indonesia has become the objective which aims the intention to analyze the effect of ESG disclosure on stock returns. This research employs secondary data sample obtained from listed firms on the Indonesia Stock Exchange (IDX) that published ESG scores between year of 2022 until 2024. A total of 228 data observations were analyzed using linear regression method. The research findings reveal a positive and statistically significant between ESG disclosure and stock returns in emerging country, Indonesia. These results support signaling theory, which suggests that the disclosure of non-financial information is able to enhance investor’s trust and confidence. Practically, the findings provide valuable higlights strategic importance of integrating ESG transparency into corporate governance management frameworks to improve the quality of ESG disclosure as a means of increasing and intensify investment attractiveness.